INTERNATIONALIZING LEGAL EDUCATION: A COOPERATIVE TOOL IN A GLOBALIZED WORLD - Williams, Jamie J. (Indonesian Journal of International Law, 2015)
The term “globalization” has been applied to everything from economics and technology to social media and market trends. Its use has become somewhat of a cliché1, and it is almost impossible to read a treatment of globalization that does not acknowledge the ambivalence and hyperbole surrounding the term. The phrase “globalization of legal education” has the power to conjure visions of sophisticated lawyers-in-the-making jockeying for positions in transnational mega firms, or interning at international courts and dreaming of combating injustice on an international scale. It has been posited that a working knowledge of the global legal landscape is as indispensible to today’s legal graduate as a working knowledge of digital technological advances.2 Can law really be taught at a global scale, or is it still the province of domestic authority? A global lawyer may work in numerous jurisdictions, or at least one different from where they were taught. How does their education prepare them for that possibility? Can a global lawyer work in foreign jurisdictions in matters of private law? Is the “globalization of legal education” just a marketing equivocation for classes conducted in a common language, or about the international legal regime – or is there something substantively and pedagogically distinctive about the endeavor? How should global legal education translate into practice in 2015? This paper endeavors to explore the intersection between globalization of law and globalization of legal education.